Robot Pengikut Target Berdasarkan Bentuk dan Warna Menggunakan Metode HSV Untuk Aplikasi Assistant Robot - Syahri Muharom; Saiful Asnawi; Affan Bachri (Jurnal JE-UNISLA : Electronic Control, Telecomunication, Computer Information and Power System, 2021)
In this era many system can be help people  doing activity. Assistant robot is a robot used to help people activity. Follower robot is a robot can follow the object automatically. From the background, the researcher created a robot can follower target based on shape and color to assistant robot application. This robot equipped with camera to detect target and microcontroller to movement robot control. To recognize object, the system will detect object based on shape and colour, then the robot will follow wherever the target moves. From the test result, the system can detect object is 86.6% successs rate, with the best lumination of light is 120 lux. Testing detection target based on distance, having result is 87,5% success rate, with minimum distance is 30 cm and maximum distance is 350 cm. from all of experiment, the robot will moves follow target while the distance of target is more then 80cm  and less than 350 cm, and the robot will stop while distance target is less then 80 cm. the researcher hope the robot can giving help people in daily activity.